The Credibility of Choi Siwon in Increasing Brand Awareness and Interest in Buying Mie Sedap Korean Spicy Noodles - Rania Sarah Syaharani; Drina Intyaswati; Rizkiya Ayu Maulida (Inter Komunika, 2022)
The entry of the Korean Wave to Indonesia certainly attracted the Indonesian people to become KPOP fans, and this was used by PT Wings Food to attract the interest of KPOP fans to attract their buying interest by making Choi Siwon a representative icon of their product, namely Mie Sedaap, the Korean Spicy Chicken variant. This research was conducted to find out whether the brand awareness of the Mie Sedaap product, the Korean Spicy Chicken variant, is able to mediate Choi Siwon's credibility in increasing the buying interest of KPOP fans. The theory used is the Source Credibility Theory. This research was conducted using a random sampling technique which was distributed to 100 people and calculated using a Likert scale with multiple linear regression analysis. The result obtained is that brand awareness of the Mie Sedaap product, the Korean Spicy Chicken variant, is able to mediate the relationship between Choi Siwon's credibility and also the buying interest of KPOP fans.